URGENSI PERATURAN UNTUK PERLINDUNGAN KONSUMEN TERHADAP PRODUK KOSMETIK YANG MEMILIKI BAHAN BERLEBIHAN DALAM PRODUKSI - Mulyanah, Dede; Ratnawati, Elfrida; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: In running a business, entrepreneurs are required to follow several written regulations established by the government and regulated by law. In the pharmaceutical industry, entrepreneurs must register their products with a specific agency, namely BPOM. The government has created regulations regarding the supervision of cosmetic circulation to protect consumers and ensure the safety of cosmetic products. These regulations are designed to address the sale of cosmetics without trading permits. This research aims to understand how supervision is implemented and why it is ineffective in protecting consumers. The methods used are normative, and the research specification is descriptive analytical. The results indicate that the supervision conducted does not meet cosmetic supervision regulations and does not encompass the stage of consumer protection. The ineffectiveness of supervision is caused by law enforcement officials who cannot follow existing government regulations, as well as low public awareness.Keywords: BPOM, Cosmetics, Consumen Protection